Less painful ESWL with ultrasound-guided quadratus lumborum block: a prospective randomized controlled study. (2nd November 2019) - Yayik, Ahmet Murat; Ahiskalioglu, Ali; Alici, Haci Ahmet; Celik, Erkan Cem; Cesur, Sevim; Ahiskalioglu, Elif Oral; Demirdogen, Saban Oguz; Karaca, Omer; Adanur, Senol
Abstract: Objectives: Extracorporeal shock wave lithotripsy (ESWL) has been widely used for the treatment of urinary tract stones and is usually administered as an outpatient procedure, although the vast majority of patients do not tolerate it without sedoanalgesia. The quadratus lumborum block (QLB) is a newly-defined technique for abdominal surgery. The aim of this study was to evaluate the analgesic efficacy of ultrasound-guided QLB in ESWL. Materials and methods: Forty patients, aged 18–65, with ASA physical status I–II and scheduled for ESWL were randomly assigned to Group C (control group) and Group QLB (treatment group). Group QLB received single-shot USG-guided transmuscular QLB with 10 ml of 0.5% bupivacaine and 10 ml of 2% lidocaine before a 20-min ESWL procedure. No intervention was performed on Group C. Visual analogue scale (VAS) scores, opioid consumption, patient satisfaction, ESWL and stone details were recorded. Results: VAS scores were significantly lower in Group QLB at all time intervals ( p <  0.05). Fentanyl consumption during ESWL was significantly lower in Group QLB than in Group C ( p <  0.001). The fragmentation success rate was significantly higher in Group QLB than in Group C (19/20 vs 14/20, respectively, p =  0.046). Patient satisfaction was also higher in Group QLB ( p =  0.011). Conclusions: This study shows that QLB provided adequate analgesia for ESWL and that it reduced extra opioid consumption significantly compared to the control group.